Avaliação do potencial de estirpes e consórcios microbianos para degradação de corantes têxteis - Rosa, Lídia Simão da (2025)
Brazil is a major power in the textile industry, encompassing everything from the cultivation of raw materials to the final stages of production and commercialization. The use of microorganisms in the treatment of wastewater contaminated with textile dyes has been widely researched, resulting in numerous studies on different treatment methodologies for these effluents. Among biological approaches, the use of microbial consortia is one of the most promising, since complementary metabolisms can lead to the complete mineralization of pollutants. In this context, this work investigated the potential application of microbial consortia in the decolorization of six dyes: the azo group dyes Golden Yellow RNL, Methyl Orange, Reactive Black N, Reactive Red CA, Reactive Brilliant Violet 5R, and the dye Indigo Carmine, which is widely used in denim dyeing processes. Six bacterial strains, previously isolated from environments contaminated with the dyes Methyl Orange and Remazol Blue and here designated as A7, C3, C5, C7.1, L3, and L7, were selected for this study and combined into 20 consortia according to antagonism and viability tests. It was demonstrated that culture conditions directly influence the degradation potential of the consortia. The decolorization tests were carried out over seven days, with aliquots taken on three alternate days for comparison and monitoring of the degradation process. The results showed that decolorization in static systems was, in most cases, superior to that in agitated systems. The highlights were consortia C3, C2, C14, and C9, respectively. Consortium C3, under static conditions, achieved a decolorization rate of 91% for Methyl Orange compared to 12% under agitation; for Reactive Red CA, the same consortium decolorized 85% without aeration and 29% with agitation. Consortium C2 showed a maximum decolorization peak of 77% (static) and 22% (agitated) for the violet dye. Consortium C14 reached its maximum decolorization of 73% (static) and 11% (agitated) for the black dye. For the yellow dye, the most difficult to degrade among those selected for this study, the maximum decolorization was achieved by consortium C9, with 56% under static conditions compared to 19% under agitation. The results highlight the superior efficiency of static systems compared to agitated ones, as well as the promising potential of consortia for the decolorization of toxic dyes. Future analyses will focus on the byproducts formed, in order to map the degradation pathways and evaluate the safety of the treated effluent.